Risk Identification and Responses of Tunnel Construction Management during the COVID-19 Pandemic - Zhimin Wang; Zixiao Liu; Junyan Liu (Advances in Civil Engineering)
The COVID-19 pandemic has brought about significant influences to the world, including tunnel construction. Based on the analysis of 12 tunnel construction projects, this paper identifies the specific risk factors related to the COVID-19 pandemic, e.g., men, materials, machines, methods, social environment, and political epidemic prevention pressure. Among these risk factors, worker availability, site accessibility, shortage of construction materials, and inadequate epidemic prevention materials caused by the lockdown policy are the most fundamental challenges encountered by the projects. Social panic and epidemic prevention policy requirements are key issues needed to be addressed before the resumption of construction work. The special circumstances caused by the COVID-19 pandemic called for flexible project management and coordination skills to raise suitable and effective response strategies, while local governments make substantial contributions in solving the difficulties. Although these measures have resulted in higher project costs, their effectiveness in catching up with project schedules is worthy of recognition. The findings of this study enrich the risk categories of tunnel construction and the risk response strategies from the perspective of a global pandemic. It implies that future construction schemes including design, budget, supply chain, and project management should consider the possible influence of an epidemic.